Rewritings, Sequels, and Cycles in Sixteenth-Century Castilian Romances of Chivalry : 'Aquella inacabable aventura'. - Gutiérrez Trápaga, Daniel (Monografías A., 2017)
Examines the importance of intertextuality, in particular hypertextuality, in the poetics of Castilian romances of chivalry.